Phylogenetic lineages of Monopterus albus (Synbranchiformes: Synbranchidae) in China inferred from mitochondrial control region. (15th October 2012) - Cai, Xin; Yu, Shumin; Mipam, Tserangdonko; Zhang, Xiuyue; Yue, Bisong
Abstract: Phylogenetic inference of mitochondrial control region (501 bp) of 167 individuals from 12 regional populations revealed that Chinese swamp eels fell into five genetic lineages, Lineage A, B, C, D and E. Lineage A was speculated to share the same mitochondrial ancestors with the populations from Taiwan Island. Lineage C harboured most of the haplotypes (39/60) of populations and may have experienced population expansion. The distribution pattern of Lineage C from east to west regions may have resulted from the occurrence of the major glaciation and inter‐regional introduction. Lineage A, B and E inhabiting coastline regions were immune from the expansion of Lineage C due to isolation from inland areas blocking gene flow between inland and coastal populations. On the other hand, Chinese swamp eels were revealed to be maintaining substantially differentiated population structures, while three populations from the Sichuan basin (MY, LC and YA) were genetically closely related. This was attributed to the geographical isolation of Sichuan populations from other populations, facilitating gene flow among the three populations from the Sichuan basin.